Making mercury-photosensitized dehydrodimerization into an organic synthetic method. Vapor-pressure selectivity and the behavior of functionalized substrates - Brown, Stephen H; Crabtree, Robert H (Journal of the American Chemical Society, 1989)
Mercury-photosensitized dehydrodimerization in the vapor phase can be make synthetically useful by taking advantage of a simple reflux apparatus, in which the products promptly condense and are protected from further conversion. This vapor pressure selectivity gives high chemical selectivity even at high conversion and on a multigram scale. Mercury absorbs 254-nm light to give the sup 3Psub 1 excited state (Hg*), which homolyses a C-H bond of the substrate with a 3{degree} > 2{degree} > 1{degree} selectivity. Quantitative prediction of product mixtures in alkane dimerization and in alkane-alkane cross-dimerizations is discussed. Radical disproportionation gives alkene, but this intermediate is recycled back into the radical pool via H atom attack, which is beneficial both for yield and selectivity. The method is very efficient at constructing C-C bonds between highly substituted carbon atoms, yet the method fails if a dimer has four sets of obligatory 1,3-syn methyl-methyl steric repulsions, as in the unknown 2,3,4,4,5,6,7-octamethyloctane. We have extended the range of substrates susceptible to the reaction, for example to higher alcohols, ethers, silanes, partially fluorinated alcohols, and partially fluorinated ethers. We see selectivity for dimers involving C-H bond {alpha} to O or N and for S-H over C-H. An important advantage of our experimental conditions in the case of alcohols is that the aldehyde or ketone disproportionation product (which is not subject to H{sup {sm bullet}} attack) is swept out of the system by the stream of Hsub 2 also produced, so it does not remain and inhibit the rate and lower the selectivity. ksub dis/ksub rec is estimated for a number of radicals studied. The very hindered 3{degree} 1,4-dimethylcyclohex-1-yl radical is notable in having a ksub dis/ksub rec as high as 7.1.